Springback-reducing sprayed concrete admixture suitable for high and cold and low temperature and application of springback-reducing sprayed concrete admixture

Through the silanized grafting technology of graphene oxide and nanochitin, the interpolymer is formed, which solves the problems of insufficient strength and high rebound rate of sprayed concrete in low temperature environments, and achieves efficient freeze-thaw resistance and construction safety.

CN119638258APending Publication Date: 2025-03-18SICHUAN HIGHWAY PLANNING SURVEY DESIGN AND RESEARCH INSTITUTE LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411994725.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the construction of high-altitude mountain tunnels, it is difficult for jet concrete to quickly achieve sufficient strength in low temperature environments, and it is prone to have a high rebound rate due to freeze-thaw cycles and harsh climatic conditions, which cannot meet the requirements of construction safety and high-quality engineering construction.

Method used

Through silanized grafting of graphene oxide (GO) and chitin nano-chitin interpolymers are formed, the tiny pores between cement hydration products are filled, the porosity is reduced, and the barrier layer is formed on the pore surface to prevent the invasion of harmful substances and enhance the anti-freeze-thaw properties.

Benefits of technology

It significantly reduces the rebound rate of concrete, improves compressive strength and freeze-thaw resistance, and ensures construction safety and engineering quality under high and low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a springback-reducing sprayed concrete admixture suitable for alpine and low temperature and application of the springback-reducing sprayed concrete admixture. The springback-reducing sprayed concrete admixture comprises the following components: 50-80 parts of a water reducing agent; 5 to 30 parts of a graphene oxide-nano chitin copolymer; 400 to 500 parts of a nano active component; 20-40 parts of an auxiliary material; and 300 to 450 parts of water. Nano chitin (ChNF) prepared by a TEMPO method is subjected to silanization modification and then is grafted with graphene oxide to obtain GO-ChNF. In the concrete, the graphene oxide, the nano chitin and the nano active component are compounded in proportion, a two-dimensional lamellar structure of GO and the nano chitin can be bridged between hydration products and cooperate with auxiliary materials to achieve a lubricating effect, the flowing working performance of the sprayed concrete is improved while the bonding performance is not lost, spraying construction is smooth, pipe blockage is avoided, and the service life of the sprayed concrete is prolonged. The construction efficiency is improved and the cost is reduced. The copolymer can reduce the porosity in the concrete by 15-20%, and can form a barrier layer on a concrete interface, thereby effectively preventing harmful substances such as moisture, chloride ions and the like from invading, protecting the internal structure of the concrete and improving the durability of a support system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of shotcrete admixtures, and in particular to a rebound-reducing shotcrete admixture suitable for high-cold and low-temperature conditions and an application thereof. Background Art

[0002] In the construction of tunnels in mountainous areas at high altitudes, there is an urgent need for shotcrete that can be quickly constructed in low-temperature environments and has good durability. In order to ensure the construction progress and long-term stability of the structure, shotcrete needs to be able to quickly reach sufficient strength in low-temperature environments and be able to withstand frequent freeze-thaw cycles and harsh climatic conditions. Low temperature conditions slow the formation of cement hydration products and the internal bonding of concrete is insufficient. When sprayed onto the sprayed surface, the concrete cannot quickly form sufficient bonding strength and is easy to fall off from the sprayed surface, resulting in an increase in the rebound rate. Compared with normal temperature conditions, the rebound rate of concrete will be 20~30% higher. Due to the harsh terrain, geology and climatic conditions of the Zheduoshan Tunnel Project, especially during winter construction, higher requirements are placed on the setting time and early strength performance of shotcrete. In addition, due to the aeolian sand geology and water gushing problems in the area, higher requirements are also placed on anti-seepage performance.

[0003] In the existing sprayed concrete admixture technology, early strength agents containing lithium salts, nitrates and other ingredients are added to accelerate the hydration reaction of cement at low temperatures. At the same time, the antifreeze performance of fiber-reinforced concrete is also being studied, such as adding carbon fiber, polypropylene fiber, etc. These fibers can form a network structure inside the concrete to prevent the expansion of cracks, but it is always impossible to take all the problems into account, and the construction safety hazards are large; the rebound rate of on-site construction is high, and the requirements of green and low-carbon high-quality engineering construction cannot be met. CN111320416 provides a low-rebound high-strength sprayed concrete strengthening agent, which uses amphiphilic nanocellulose combined with plant polysaccharides to achieve the effect of reducing the rebound rate and improving the performance of concrete, but under extreme conditions, the solubility of plant polysaccharides is reduced and even phase separation occurs, which destroys the rheological properties of the mortar and cannot achieve functions and effects similar to those under conventional conditions. Summary of the invention

[0004] The present invention provides a rebound-reducing shotcrete admixture suitable for high-cold and low-temperature environments. Through the silanization grafting of graphene oxide (GO) and nano-chitosan (ChNF), the two-dimensional lamellar structure of GO can fill the tiny pores between cement hydration products, and the nano-chitosan can bridge the pores like fibers. The synergistic effect of the two reduces the porosity inside the concrete and forms a barrier layer on the surface of the pores, effectively preventing the intrusion of harmful substances such as moisture and chloride ions. The fiber characteristics of ChNF effectively prevent the expansion of cracks and prevent the internal structure of the concrete from being destroyed due to freeze-thaw expansion.

[0005] The technical solution of the present invention: A rebound-reducing shotcrete admixture suitable for high-cold and low-temperature environments, comprising the following components in parts by weight: Water reducing agent 50-80 parts; 5-30 parts of graphene oxide-nano-chitin copolymer; 400-500 parts of nano active components; 20-40 parts of auxiliary materials; 300-450 parts of solvent water.

[0006] Furthermore, the water reducer is an early-strength polycarboxylic acid water reducer, the molecular weight of the polyether macromonomer is greater than 4000, and the acid-ether ratio is 4.5-6:1.

[0007] Furthermore, the nano-active component includes one or more of nano-silicon dioxide, nano-alumina, and nano-hydrated calcium silicate.

[0008] Furthermore, the auxiliary materials include an early strength agent, a rheology regulator, an accelerating setting agent, and a stabilizer.

[0009] Furthermore, the early strength agent includes one or more of lithium silicate, lithium hydroxide, diethanolamine, triethanolamine, triisopropanolamine, and calcium formate; the rheology regulator is one or more of xanthan gum, guar gum, Weinlun gum, polyethylene glycol 2000, polyacrylic acid, hydroxymethyl cellulose ether, and ethylene-vinyl acetate copolymer emulsion; the accelerator is an alkali-free accelerator; the stabilizer includes one or more of polyvinyl alcohol, bentonite, Tween-80, sodium sulfite, sodium citrate, sodium carboxymethyl cellulose, sodium dodecylbenzene sulfonate, sodium methacrylic acid, and azobisisobutyronitrile.

[0010] Furthermore, the preparation method of the graphene oxide-nano-chitin copolymer specifically comprises the following steps: (1) Preparation of graphene oxide by Hummers method; (2) Preparation of nano-chitosan by TEMPO method: TEMPO and NaBr were dissolved in deionized water, chitosan raw material was added, and after stirring and soaking, NaClO solution was added to initiate oxidation reaction; NaOH solution was added dropwise to control the pH value to 10-11 until the pH value no longer changed and the reaction was terminated; the oxidized chitosan was separated by plate and frame filter press, and after washing, high-pressure homogenization was used to achieve nanofiberization to obtain nano-chitosan.

[0011] (3) Silanized modified nano-chitin: After ultrasonic treatment of nano-chitin, a 0.3wt% nano-chitin suspension is prepared with deionized water; a silane coupling agent solution is prepared using 0.15-0.30wt% silane coupling agent and ethanol solution, and the nano-chitin suspension is added after sufficient stirring and hydrolysis. After ultrasonic treatment for 1-2h, mechanical stirring is maintained at 60-80°C for 2-6h; after washing and drying with deionized water and anhydrous ethanol, silanized nano-chitin is obtained.

[0012] (4) Graphene oxide grafted nano-chitin copolymerization: add carboxylic acid activator to graphene oxide, stir thoroughly to generate activated ester, add silanized nano-chitin, ultrasonically treat for 1-2 hours, and maintain mechanical stirring for 2-6 hours; wash with deionized water and anhydrous ethanol and dry to obtain graphene oxide-nano-chitin copolymer.

[0013] Furthermore, the Hummers method for preparing graphene oxide specifically comprises the following steps: S11: In an ice bath, graphite powder is added to concentrated sulfuric acid, stirred evenly, and then sodium nitrate and potassium permanganate are added, the reaction temperature is controlled not to exceed 20° C., and stirring is continued to obtain a dark green mixture; S12: transferring the dark green mixture to a warm water bath, controlling the temperature not to exceed 50° C., and continuously stirring to obtain a brown paste mixture; raising the temperature of the reaction system to 80° C., slowly dropping deionized water into the brown paste mixture, and continuously stirring to obtain a yellow solution; S13: adding an appropriate amount of hydrogen peroxide solution to the yellow solution to reduce unreacted potassium permanganate until the solution turns bright yellow and the reaction is complete; subjecting the product after the reaction to high-speed centrifugation, washing, and drying to obtain graphene oxide.

[0014] Furthermore, in step 2), the amount of TEMPO used is 0.1-1% of the mass of chitin; the amount of NaBr used is 1-5% of the mass of chitin; the mass ratio of the chitin raw material to the NaClO solution is 1:(3-7); the mass ratio of the chitin raw material to deionized water is 1:(40-200). The chitin raw material is the shell of a crustacean, which has been decalcified, deproteinized, and decolorized.

[0015] Furthermore, the silane coupling agent in step 3) includes one or more of 3-aminopropyltriethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, and γ-(methacryloyloxy)propyltrimethoxysilane.

[0016] Furthermore, the carboxylic acid activating agent is one or more of ethyl chloroformate, isobutyl ester, nitrophenyl ester, pentafluorophenyl ester, and N-hydroxysuccinimide ester.

[0017] A rebound-reducing shotcrete admixture suitable for high-cold and low-temperature environments, the preparation method of which comprises the following steps: (1) Dissolve the graphene oxide-nano-chitin copolymer in solvent water and heat it in a water bath at 60°C to fully swell; (2) mixing the graphene oxide-nano-chitin copolymer solution, the water reducing agent, and the auxiliary materials, and then continuously stirring for 24 hours to age to obtain a mixed solution; (3) Adding the nano-active component into the mixed liquid and stirring thoroughly to obtain a rebound-reducing shotcrete admixture.

[0018] As a preferred solution, in shotcrete construction, the amount of the rebound-reducing shotcrete admixture suitable for high-cold and low-temperature conditions is 5-8% of the total cementitious material mass.

[0019] Beneficial effects of the present invention: 1) Both graphene oxide and nano-chitosan have high specific surface areas. In concrete, the two-dimensional layered structure of GO can fill the tiny pores between cement hydration products, and nano-chitosan can bridge the pores. The synergistic effect of the two reduces the porosity of concrete by 15-20% and increases the compressive strength by 20-30%.

[0020] 2) Graphene oxide, nano-chitin and nano-active components are compounded in proportion to fill the pores of concrete and form a barrier layer on the surface of the pores. This barrier layer can effectively prevent the intrusion of harmful substances such as water and chloride ions. The chloride ion permeability is reduced by about 48% compared with the blank benchmark. At the same time, it reduces the expansion force generated by water freezing, protects the internal structure of concrete, and significantly improves the anti-freeze and thaw performance.

[0021] 3) Nano-chitosan has good water absorption and provides sufficient water for cement hydration reaction. When the graphene oxide-nano-chitosan copolymer is adjusted with auxiliary materials, the graphene oxide sheet structure plays a lubricating role. Without losing the bonding performance, it improves the flow performance of shotcrete, and the spraying construction is smooth without pipe clogging, which reduces construction costs and improves construction efficiency.

[0022] 4) Compared with plant polysaccharides and nanocellulose, the glycosidic bonds in chitosan molecules are relatively stable in low-temperature environments (such as -20°C to 0°C) and will not break easily. By combining with graphene oxide, the functional groups on the surface of nano-chitosan are chemically modified to increase the steric hindrance of nano-chitosan particles at low temperatures, prevent interaction and agglomeration between nano-chitosan particles, and ensure the stability of material properties under low-temperature freeze-thaw conditions. DETAILED DESCRIPTION

[0023] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. In this application, unless otherwise specified, all percentage contents are mass percentages.

[0024] The present invention provides a low-rebound shotcrete admixture suitable for high-cold and low-temperature environments and its application. Graphene oxide and nano-chitosan are prepared respectively by the Hummers method and the TEMPO oxidation method. Graphene oxide and nano-chitosan are grafted by a silane coupling agent. The graphene oxide-nano-chitosan copolymer and nano-calcium silicate hydrate in the following embodiments are prepared by the following method: Preparation of graphene oxide by Hummers method: In an ice bath, add 2g of 5000-mesh graphite powder to 25ml of concentrated sulfuric acid, stir evenly, add 1g of sodium nitrate and 6g of potassium permanganate, control the reaction temperature not to exceed 20°C, continue stirring for 2h, and obtain a dark green mixture; heat to 35°C, continue stirring for 30min, the oxidation process between graphite layers is positive, the structure becomes loose, and a brown paste mixture is obtained; add 50ml of deionized water to the reaction system, continue stirring for 20min, and the oxidant further React with graphite to promote the hydrolysis of graphite interlayer compounds, the temperature of the reaction solution increases, and the reaction solution turns yellow; continue to add an appropriate amount of hydrogen peroxide solution to reduce the residual oxidant until the solution turns bright yellow and the reaction is complete, and the hydrogen peroxide solution further oxidizes the graphite to increase the oxygen-containing functional groups on its surface; the product after the reaction is centrifuged at high speed, washed with 5% HCl and deionized water until no sulfate is detected, and dried in a 60°C vacuum drying oven to obtain graphene oxide, and the obtained graphene oxide has a thickness of ≤5nm and a sheet diameter of 20μm.

[0025] Preparation of nano-chitin by TEMPO method: 1.5 g TEMPO and 12 g NaBr were weighed and dissolved in 4.54 kg deionized water, 0.1 kg chitin raw material was added, stirred and swollen, 0.35 kg NaClO was added to react for 4 h, and NaOH solution was added dropwise during the reaction to adjust the pH of the reaction system to 10.2. After the reaction, the oxidized chitin slurry was separated by a plate-and-frame filter, the oxidized chitin slurry was mechanically treated, and homogenized 10 times at a pressure of 70 MPa to obtain nano-chitin.

[0026] Silanized modified nano-chitin: After ultrasonic treatment of nano-chitin, a 0.3wt% nano-chitin suspension is prepared with deionized water; a silane coupling agent solution is prepared with 0.16wt% 3-aminopropyltriethoxysilane and ethanol solution, and the above nano-chitin suspension is added after sufficient stirring and hydrolysis. After ultrasonic treatment for 2h, mechanical stirring is maintained at 65°C for 6h; after washing and drying with deionized water and anhydrous ethanol, silanized nano-chitin is obtained.

[0027] Preparation of nano calcium silicate hydrate: Heat the dispersant to 60°C, mix evenly, and then cool, and simultaneously add calcium nitrate solution and sodium metasilicate solution to the dispersion, with a calcium-silicon ratio of 3:2, and stir continuously to obtain nano calcium silicate hydrate. The dispersant includes a polyether monomer with a molecular weight greater than 4000, a stabilizer polyethylene glycol, a chain transfer agent thioglycolic acid, a reducing agent ammonium persulfate, and an initiator diacyl peroxide. Example

[0028] A rebound-reducing shotcrete admixture suitable for high-cold and low-temperature environments, comprising: Polycarboxylate water reducer: 60 parts; Graphene oxide-nano-chitin copolymer: 20 parts; Nano hydrated calcium silicate: 480 parts; Auxiliary materials: 30 parts, early strength agent lithium silicate 8 parts, diethanolamine 10 parts, accelerate the early strength development of concrete and shorten the support molding time; rheology regulator is xanthan gum 6 parts, Wenlun glue 6 parts, so that the concrete is easy to pump and pour in a small space and maintain good rheological properties; alkali-free quick-setting agent 10 parts to ensure that the concrete solidifies in time to prevent the collapse of the well wall; stabilizer is polyvinyl alcohol 4 parts, sodium citrate 4 parts, maintain the stability of concrete and avoid quality problems in complex environments.

[0029] Solvent water: 380 parts. Example

[0030] A rebound-reducing shotcrete admixture suitable for high-cold and low-temperature environments, comprising: Polycarboxylate water reducer: 70 parts; Graphene oxide-nano-chitin copolymer: 25 parts; Nano hydrated calcium silicate: 460 parts; Auxiliary materials: 30 parts, early strength agent is lithium hydroxide 8 parts, calcium formate 10 parts, accelerate the early strength development of concrete to meet the needs of rapid construction in high-altitude cold areas; rheology regulator is Wenlun glue 6 parts, hydroxymethyl cellulose ether 4 parts, to ensure the fluidity of concrete during low-temperature pumping; accelerator uses high-efficiency alkali-free accelerator 10 parts to shorten the setting time of concrete and reduce the risk of freezing; stabilizer is polyvinyl alcohol 6 parts, sodium sulfite 4 parts to maintain the stability of the concrete system and prevent cracks at low temperatures.

[0031] Solvent water: 400 parts.

[0032] Preparation steps of rebound-reducing shotcrete admixture: (1) Dissolve the graphene oxide-nano-chitin copolymer in solvent water and heat it in a water bath at 60°C to fully swell; (2) According to the components provided in the above embodiment, the graphene oxide-nano-chitin copolymer solution, the water reducing agent and the auxiliary materials are mixed and stirred for 24 hours to obtain a mixed solution; (3) Adding the nano-active component into the mixed liquid and stirring thoroughly to obtain a rebound-reducing shotcrete admixture.

[0033] The amount of rebound reducing sprayed concrete admixture is 7%, and the sprayed concrete mortar is prepared according to the mix proportion in Table 1, and the process test is carried out. The admixture dosage of the control group is 1% of the water reducer and 6% of the accelerator.

[0034]

[0035] The test results of the working performance of shotcrete slurry are shown in Table 2 below.

[0036]

[0037] In a low temperature environment (5°C), the test results of the spraying construction performance are shown in Table 3 below.

[0038]

[0039] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A rebound-reducing sprayed concrete admixture suitable for high-cold and low-temperature environments, characterized in that The following components are included by weight: Water reducing agent 50-80 parts; 5-30 parts of graphene oxide-nano-chitin copolymer; 400-500 parts of nano active components; 20-40 parts of auxiliary materials; 300-450 parts of solvent water.

2. The rebound-reducing sprayed concrete admixture suitable for high-cold and low-temperature environments according to claim 1, characterized in that The water reducer is an early strength polycarboxylic acid water reducer, the molecular weight of the polyether macromonomer is greater than 4000, and the acid-ether ratio is 4.5-6:

1.

3. The rebound-reducing sprayed concrete admixture suitable for high-cold and low-temperature environments according to claim 1, characterized in that The nano active component includes one or more of nano silicon dioxide, nano aluminum oxide, and nano calcium silicate hydrate.

4. The rebound-reducing sprayed concrete admixture suitable for high-cold and low-temperature environments according to claim 1, characterized in that The auxiliary materials include an early strength agent, a rheology regulator, an accelerating setting agent, and a stabilizer; the early strength agent includes one or more of lithium silicate, lithium hydroxide, diethanolamine, triethanolamine, triisopropanolamine, and calcium formate; the rheology regulator is one or more of xanthan gum, guar gum, Weinlun gum, polyethylene glycol 2000, polyacrylic acid, hydroxymethyl cellulose ether, and ethylene-vinyl acetate copolymer emulsion; the accelerating setting agent is an alkali-free accelerating setting agent; the stabilizer includes one or more of polyvinyl alcohol, bentonite, Tween-80, sodium sulfite, sodium citrate, sodium carboxymethyl cellulose, sodium dodecylbenzene sulfonate, sodium methacrylic acid, and azobisisobutyronitrile.

5. The rebound-reducing sprayed concrete admixture suitable for high-cold and low-temperature environments according to claim 1, characterized in that The method for preparing the graphene oxide-nano-chitin copolymer comprises the following steps: (1) Preparation of graphene oxide by Hummers method; (2) Preparation of nano-chitosan by TEMPO method: TEMPO and NaBr are dissolved in deionized water, chitosan raw materials are added, and after stirring and soaking, NaClO solution is added to initiate oxidation reaction; NaOH solution is added dropwise to control the pH value to 10.0-10.5 until the pH value no longer changes and the reaction is completed; the oxidized chitosan is separated by a plate and frame filter press, and after washing, high-pressure homogenization is used to achieve nanofiberization to obtain nano-chitosan; (3) Silylation-modified nano-chitin: After ultrasonic treatment of the nano-chitin obtained in step 2), a 0.3 wt% nano-chitin suspension is prepared with deionized water; a silane coupling agent solution is prepared by using 0.15-0.30 wt% of a silane coupling agent and an ethanol solution, and the nano-chitin suspension is added after sufficient stirring and hydrolysis, and ultrasonic treatment is performed for 1-2 hours, and mechanical stirring is maintained at 60-80° C. for 2-6 hours; after washing and drying with deionized water and anhydrous ethanol, a silanized nano-chitin is obtained; (4) Graphene oxide grafted nano-chitin copolymerization: add a carboxylic acid activator to the graphene oxide obtained in step 1), stir thoroughly to generate an activated ester, add the silanized nano-chitin obtained in step 3), ultrasonically treat for 1-2 hours, and then maintain mechanical stirring for 2-6 hours; wash with deionized water and anhydrous ethanol and dry to obtain a graphene oxide-nano-chitin copolymer.

6. The rebound-reducing sprayed concrete admixture suitable for high-cold and low-temperature environments according to claim 5, characterized in that The Hummers method for preparing graphene oxide is specifically as follows: S11: In an ice bath, graphite powder is added to concentrated sulfuric acid, stirred evenly, and then sodium nitrate and potassium permanganate are added, the reaction temperature is controlled not to exceed 20° C., and stirring is continued to obtain a dark green mixture; S12: transferring the dark green mixture to a warm water bath, controlling the temperature not to exceed 50° C., and continuously stirring to obtain a brown paste mixture; raising the temperature of the reaction system to 80° C., slowly dropping deionized water into the brown paste mixture, and continuously stirring to obtain a yellow solution; S13: adding an appropriate amount of hydrogen peroxide solution to the yellow solution to reduce unreacted potassium permanganate until the solution turns bright yellow and the reaction is complete; subjecting the product after the reaction to high-speed centrifugation, washing, and drying treatment to obtain graphene oxide.

7. The rebound-reducing sprayed concrete admixture suitable for high-cold and low-temperature environments according to claim 5, characterized in that In the step 2), the amount of TEMPO used is 0.1-1% of the mass of chitin; the amount of NaBr used is 1-5% of the mass of chitin; the mass ratio of chitin to NaClO solution is 1:(3-7); the mass ratio of chitin raw material to deionized water is 1:(40-200); the chitin raw material is the shell of crustaceans, which has been decalcified, deproteinized and decolorized.

8. The rebound-reducing sprayed concrete admixture suitable for high-cold and low-temperature environments according to claim 5, characterized in that In the step 3), the silane coupling agent includes one or more of 3-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and γ-(methacryloyloxy)propyltrimethoxysilane; in the step 4), the carboxylic acid activator is one or more of ethyl chloroformate, isobutyl ester, nitrophenyl ester, pentafluorophenyl ester, and N-hydroxysuccinimide ester.

9. A rebound-reducing shotcrete admixture suitable for high-cold and low-temperature environments as claimed in any one of claims 1 to 8, characterized in that The preparation method comprises the following steps: (1) dissolving the graphene oxide-nano-chitin copolymer in solvent water and heating in a water bath at 60° C. to fully swell; (2) mixing the graphene oxide-nano-chitin copolymer solution, the water reducing agent, and the auxiliary materials, and then continuously stirring for 24 hours to age to obtain a mixed solution; (3) Adding the nano-active component into the mixed liquid and stirring thoroughly to obtain a rebound-reducing shotcrete admixture.

10. The use of a rebound-reducing sprayed concrete admixture suitable for high-cold and low-temperature environments as claimed in any one of claims 1 to 8, characterized in that The amount of the rebound-reducing shotcrete admixture provided by the present invention is 5-8% of the total mass of the cementitious material.

Citation Information

Cited By

  • Supramolecular material for improving compression resistance, drop and resilience of sprayed concrete and preparation method of supramolecular material

    CN120842594A